IPTEK BAGI MASYARAKAT MESIN PENGIRIS BAKAL KEMPLANG DI DESA PENYAMUN - Pristiansyah Pristiansyah; Falah Yudha Hanafi; Muhammad Haritsah Amrullah; Zulfitriyanto Zulfitriyanto; Hasdiansah Hasdiansah (Jurnal Pengabdian Masyarakat Polmanbabel, 2023)
Kemplang is a typical Bangka Belitung food made from mackerel or machete fish, and can also be made from squid, shrimp and sago. Kemplang has a round shape with a savory and crunchy taste when bitten. Kemplang can be consumed directly and can also be combined with typical Bangka Belitung shrimp paste which will make the taste of kemplang more diverse. The method of implementation at the completion of this final project is outlined on the flow chart. Conceptualizing a method like this has the aim that the work to be done is more directed so that what is done runs smoothly. Engine design using the VDI 2222 method makes it easier for designers to make machine designs so that they get a kemplang slicer design that can slice kemplang. PKK in penyamun village have difficulty in the process of slicing kemplang because they still use human labor, non-uniform kemplang slices and the time required in the slicing process is long. The slicing machine will be kemplang which is driven by an electric motor can slice 5 kemplang butts with a length of 30 cm and a diameter of 50 cm, and is also able to produce kemplang sheets with a thickness of ± 2 mm with a capacity of 20 kg / hour.